Physical activity in rehabilitation practice: Policy, infrastructure and development perspectives - Onika Makaula; Ntandoyenkosi L. Msomi; Andrew J. Ross (South African Family Practice)
Background: Integrating physical activity (PA) into rehabilitation practice is critical for promoting patient recovery and high quality of life. However, policy gaps, infrastructure constraints and resource limitations often hinder its effective implementation, particularly in public health care settings.